Method for liquid phase deposition of thick coating on metal surface and application thereof

By applying a high-pressure pulse electric field on the metal surface, efficient deposition of metal ions is achieved, forming a dense thick coating, solving the problems of thin coating and low binding force in the prior art, and achieving efficient and dense thick metal coating deposition .

CN119433647APending Publication Date: 2025-02-14JIANGSU JICUI SURFACE ENGINEERING TECHNOLOGY RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411622306.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, when preparing a metal surface thick coating, there are problems such as low binding force between the coating and the substrate, tiny pinholes and cracks in the coating, and the inability to deposit a coating with a thickness greater than 100 μm.

Method used

Using high-pressure liquid phase ion deposition technology, a high-voltage pulse electric field of 100-3000V is formed on the metal surface to promote the migration and deposition of metal ions to the cathode, forming a thick metal coating with dense structure and strong bonding force with the substrate.

Benefits of technology

A dense thick coating is achieved with a metal surface deposited, the coating thickness can reach 600μm, and the bonding strength with the substrate is significantly improved, solving the problems of thin coating and low binding force in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433647A_ABST
    Figure CN119433647A_ABST
Patent Text Reader

Abstract

The invention discloses a method for liquid-phase deposition of a thick coating on a metal surface and application of the method, and belongs to the technical field of surface treatment. The method comprises the following steps that S01, matrix metal is cleaned up and dried; s02, applying a strong electric field generated by 100-3000V high-voltage pulse electricity between two electrodes of the matrix metal and the M metal which are placed in the low-temperature and low-concentration metal ion Mn < + > plating solution; and S03, after deposition is completed, the metal thick plating layer which is compact in structure and high in binding force with the base body is obtained. According to the method, the pulse voltage of 100-3000V is applied, metal cations in the solution can obtain the maximum energy of 3000eV under the action of a high-potential electric field, the high-energy ions bombard a cathode metal part, the bonding performance of a coating and a matrix is improved, meanwhile, the coating can be more compact, and the service life of the coating is prolonged. And the problems of low binding force between the coating and the substrate, non-compactness of the coating, incapability of depositing a thick plating layer and the like in the existing electroplating coating are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for depositing a coating on a metal surface, in particular to a method for depositing a thick coating on a metal surface in liquid phase and application thereof, and belongs to the technical field of surface treatment. Background Art

[0002] People usually call coatings with a thickness greater than 100μm thick coatings, and the main methods for preparing thick coatings include CVD, PVD, thermal spraying, cold spraying, laser cladding, vacuum melting, etc.

[0003] The CVD method deposits a metal or metal compound coating on the substrate surface through a chemical reaction in a high temperature environment. Since the substrate is in a high temperature environment, a coating with a strong bonding force with the substrate and a thickness greater than 100μm can be deposited on the substrate surface. However, since the substrate material is in a high temperature environment during deposition, the deformation of the substrate is large.

[0004] Although the PVD method can produce a coating with a thickness greater than 100 μm, the stress generated by the deposition process of the thick coating is very large, and the bonding force between the coating and the substrate is not strong.

[0005] The thickness of thick coatings prepared by thermal spraying is generally thicker, usually between 100μm and 500μm. The preparation of ceramic coatings such as alumina and zirconia is its strength, but when preparing metal coatings, the metal particles are oxidized in the flame or plasma, so the oxygen content in the coating is very high.

[0006] Cold spraying can produce metal coatings such as copper and titanium, but there are also problems such as high oxygen content in the coating and low bonding strength between the coating and the substrate.

[0007] Laser cladding uses the energy of a laser beam to melt the material and deposit it on the surface of the substrate. The coating is metallurgically bonded to the substrate. The thickness of the prepared coating is usually 100μm to 1500μm. If multiple remelting is performed, the coating thickness will be thicker. However, there are defects such as cracks in the laser cladding coating, which affect the performance of the coating.

[0008] The vacuum melting method is to melt the coating material pre-coated on the substrate surface at high temperature under vacuum conditions, spread it on the substrate surface, and form a coating. This method is relatively easy to deposit low-melting-point metal materials such as Al, Mg, Ag, and Cu, but it is very difficult to deposit high-melting-point materials such as Ni, Cr, W, and Mo. Due to the low surface tension of molten metal and the capillary effect, the coverage range of the molten coating material is very difficult to control. In order to improve the controllability of the coverage range, refractory metal materials that are not easy to melt are often added to the coating material to form a liquid-solid co-deposition situation. When the coating is cooled, due to the difference in expansion coefficient, internal cracks are formed in the coating. Therefore, it is difficult to prepare a thick, crack-free metal coating.

[0009] As we all know, electroplating is to use the principle of electrolysis to plate a layer of metal or alloy coating (plating) with a thickness of 10 to 50 μm on the metal surface. This metal or alloy coating can improve the corrosion resistance, wear resistance, decorativeness, etc. of the base metal, and has been widely used in many industrial fields. The principle of electroplating is that in a plating tank filled with electroplating solution, the specially pre-treated part to be plated is used as the cathode, and the plated metal is used to make the anode. The two poles are connected to the positive and negative poles of the power supply respectively. After power is turned on, the metal ions in the electroplating solution migrate to the cathode under the action of a potential difference of several volts to tens of volts, forming a coating on the surface of the metal to be plated. Research has found that electroplating technology has the following characteristics:

[0010] (1) The power supply used is a low-voltage, high-current DC or pulse power supply. The voltage applied between the anode and cathode is low, ranging from a few volts to tens of volts, while the current density is high, reaching a maximum of 500A / dm 2 .

[0011] (2) The solution containing metal ions in the electroplating tank has a high concentration and good conductivity. Under the action of a very small voltage, a large current can flow through the solution.

[0012] (3) During electroplating, the electroplating solution usually needs to be heated, and sometimes the plating solution temperature is required to reach 80°C to produce a high-quality coating.

[0013] (4) Metal ions gain electrons at the cathode and are reduced to metals, which accumulate in an atomic state on the surface of the metal to be plated, forming a coating containing several tiny pinholes and other defects. If the process parameters are not well controlled, a loose coating shaped like a sponge will be produced.

[0014] (5) The bonding strength between the electroplating layer and the base metal is low, and the plating layer is easy to fall off.

[0015] (6) It is impossible to deposit a coating with a thickness greater than 100 μm.

[0016] By analyzing the above characteristics of the electroplating process, it was clarified that the current existing electroplating technology has shortcomings such as low bonding strength between the coating and the substrate, tiny pinholes in the coating, and inability to deposit thick coatings. A method for high-voltage liquid-phase ion deposition of thick coatings was invented. Summary of the invention

[0017] The object of the present invention is to provide a method for depositing a thick coating on a metal surface in liquid phase, which forms a thick metal coating with a dense structure and strong bonding with a substrate on the metal surface.

[0018] At the same time, the present invention provides an application of a method for liquid phase deposition of thick coating on a metal surface in a composite material. Since the composite material has a thicker coating, it has higher wear resistance and corrosion resistance. The composite material can be used in high-end equipment, including marine equipment such as ships and warships, wind turbines, and nuclear power plant equipment.

[0019] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0020] A method for depositing a thick coating on a metal surface from a liquid phase, comprising the following steps:

[0021] S01, cleaning and drying the base metal;

[0022] S02, in a low temperature, low concentration of metal ions M n+ A strong electric field generated by 100-3000V high-voltage pulse electricity is applied between the two electrodes of the base metal and the M metal in the plating solution; the distance between the base metal and the M metal is kept greater than 10mm;

[0023] S03, after the deposition is completed, a thick metal coating with a dense structure and strong bonding with the substrate is obtained.

[0024] Preferably, the low temperature is 24-26°C, 25-40°C or 45-55°C.

[0025] Preferably, the M metal is a soluble metal anode or an insoluble anode; the base metal is a steel metal part cathode; the anode and the cathode are respectively connected to the positive electrode and the negative electrode of a high-voltage direct current or high-voltage pulse power source.

[0026] Preferably, the metal ion M n+ Including copper ions, nickel ions or chromium ions.

[0027] Preferably, the metal ion M n+ The concentration is not more than 60g / L.

[0028] Preferably, the thick coating has a thickness greater than 100 μm.

[0029] Preferably, the method for depositing a copper coating comprises the following steps: cathode: steel metal part; anode: pure copper plate; plating solution formula: copper sulfate CuSO 4 ﹒ 5H 2 O: 1~5g / L; sulfuric acid H 2 SO 4 :0.2~0.6g / L; Sodium dodecyl sulfate: 0.05~0.1g / L; Cathode current density D k :0.1~0.4A / dm 2; Plating solution temperature: 24-26°C; deposition time: 130-300 minutes; the thickness of the deposited metal copper is 116-590 μm, the deposited layer is dense, and the bonding strength with the base metal is greater than 70 MPa.

[0030] Preferably, the method for depositing a nickel coating comprises the following steps: cathode: steel metal part; anode: electrolytic nickel plate; plating solution formula: nickel sulfate NiSO 4 ﹒ 6H 2 O: 10~50g / L; Nickel chloride NiCl 2 ﹒ 6H 2 O: 1~5g / L; sodium dodecyl sulfate: 0.05~0.1g / L; cathode current density D k :0.1~0.6A / dm 2 , plating solution temperature: 25-40°C; deposition time is 120-190 minutes; the thickness of the deposited metal nickel is 105-280 μm, the deposited layer is dense, and the bonding strength with the base metal is greater than 100 MPa.

[0031] Preferably, the method for depositing chromium coating comprises the following steps: cathode: steel metal part; anode: powder metallurgy chromium plate; plating solution formula: chromic anhydride CrO 3 :10~60g / L; sulfuric acid H 2 SO 4 :0.3~0.4g / L; cathode current density D k :0.5~0.7A / dm 2 ; Plating solution temperature: 45-55°C; deposition time: 90-200 minutes; the thickness of the deposited metal nickel is 102-130 μm, the deposited layer is dense, and the bonding strength with the base metal is greater than 80 MPa.

[0032] The invention discloses a method for depositing thick coating on metal surface by liquid phase deposition, and obtains the thick coating on metal surface by liquid phase deposition. The bonding strength between the thick coating and the base metal is 70-156 MPa, and the thickness of the coating is 102-590 μm.

[0033] The invention discloses an application of the thick coating deposited on the metal surface by liquid phase in composite materials.

[0034] Composite materials include steel-copper composite materials, steel-nickel composite materials, and steel-chromium composite materials.

[0035] The composite material of the present invention is used in high-end equipment, including marine equipment such as ships and vessels, wind turbines and nuclear power plant equipment, etc.

[0036] A method for depositing a thick coating on a metal surface in liquid phase. Pre-plated metal cations in a solution obtain high energy due to a strong electric field, are captured by a cathode and deposited on the cathode surface, forming a thick metal coating with a high bonding strength with a substrate and a dense structure and a thickness greater than 100 μm on the cathode surface.

[0037] The strong electric field is generated by applying a pulse voltage of 100 to 3000 V between a cathode and an anode placed in a conductive solution.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] The present invention discloses a method for liquid phase deposition of thick coating on metal surface and its application. The preparation method comprises the following steps: firstly, the metal is cleaned and dried, and then placed in a solution containing pre-plated metal ions and connected to the cathode of a high voltage pulse power supply; the cleaned and dried metal is placed in a solution containing pre-plated metal ions and connected to the anode of a pulse power supply; a strong electric field generated by an external pulse voltage of 100 to 3000V is generated between the cathode and the anode placed in the solution containing metal ions, and under the action of the strong electric field, the metal ions move toward the cathode and are captured by the cathode metal surface and deposited on the cathode metal surface to form a densely structured and thick metal coating with strong bonding with the substrate. The copper plating layer deposited by the method has a thickness of 116 to 590 μm, and a bonding strength (tensile strength) with a substrate greater than 70 MPa; the nickel plating layer deposited has a thickness of 105 to 280 μm, and a bonding strength (tensile strength) with a substrate greater than 100 MPa; the chromium plating layer deposited has a thickness of 102 to 130 μm, and a bonding strength (tensile strength) with a substrate greater than 80 MPa.

[0040] The present invention utilizes the effect of high electric field to deposit dense metal layer, and does not form plasma discharge. Compared with the existing electroplating technology, the present invention converts low voltage into high voltage, improves the energy of metal ions under the action of electric field, and makes the deposited metal coating have good bonding performance and thicker thickness. In order to increase the voltage, the solubility of the solution is low, and in order to supplement the problem that the metal ions in the solution are reduced due to deposition on the surface of the workpiece, high-voltage anodic etching is performed. The coating thickness deposited by the present invention using this method can reach 600μm, which cannot be achieved using current electroplating technology. The continuous provision of metal ions by anodic etching in the present invention is only one aspect of the long thick coating, and the stress of the deposited coating and the bonding strength with the metal substrate are also important contents of the long thick coating. Therefore, the electroplated coating with a non-dense structure and defects such as tiny pinholes in the prior art will not grow thick even if the deposition time is longer. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 It is a schematic diagram of the principle of the present invention;

[0042] Figure 2 It is the microstructure diagram of the copper coating on the steel surface of the present invention. DETAILED DESCRIPTION

[0043] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. The following embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0044] Example 1

[0045] A method for depositing a thick coating on a metal surface by liquid phase deposition,

[0046] Copper deposition example:

[0047] Cathode: Steel metal parts;

[0048] Anode: pure copper plate;

[0049] Plating solution formula: copper sulfate (CuSO 4 ﹒ 5H 2 O): 2~10g / L; sulfuric acid (H 2 SO 4 ): 0.2~0.6g / L; sodium dodecyl sulfate: 0.05~0.1g / L; cathode current density D k :0.1~0.4A / dm 2 ; Bath temperature: 25~40℃;

[0050] Copper deposition process 1: temperature controlled at 24°C, cathode area 10dm 2 , the main components of the solution: copper sulfate (CuSO 4 ﹒ 5H 2 O): 1g / L, sulfuric acid (H 2 SO 4 ): 0.2g / L, sodium dodecyl sulfate: 0.05g / L, power pulse frequency is 100Hz, duty cycle is 5%, current intensity is 1A (D k =0.1A / dm 2 ), the voltage varied from 880 to 1000 V, and the deposition time was 160 minutes. The deposited copper thickness was 116 μm, the deposited layer was dense, and the bonding strength (tensile strength) with the substrate was 70 MPa.

[0051] Copper deposition process 2: temperature controlled at 26°C, cathode area 10dm 2 , the main components of the solution: copper sulfate (CuSO 4 ﹒ 5H 2 O): 5g / L, sulfuric acid (H 2 SO 4): 0.6g / L, sodium dodecyl sulfate: 0.1g / L, power pulse frequency is 2000Hz, duty cycle is 95%, current intensity is 2.5A (Dk = 0.25A / dm 2 ), the voltage varied from 600 to 800 V, and the deposition time was 130 minutes. The thickness of the deposited copper was greater than 122 μm, the deposited layer was dense, and the bonding strength (tensile strength) with the substrate was 79 MPa.

[0052] Copper deposition process 3: temperature controlled at 25°C, cathode area 10dm 2 , the main components of the solution: copper sulfate (CuSO 4 ﹒ 5H 2 O): 2.5 g / L, sulfuric acid (H 2 SO 4 ): 0.3g / L, sodium dodecyl sulfate: 0.08g / L, power pulse frequency is 800Hz, duty cycle is 30%, current intensity is 4A (Dk = 0.4A / dm 2 ), the voltage varied from 2500 to 3000 V, and the deposition time was 300 minutes. The thickness of the deposited copper was greater than 590 μm, the deposited layer was dense, and the bonding strength (tensile strength) with the substrate was 103 MPa.

[0053] The main ideas of the present invention are as follows:

[0054] In the presence of low concentrations of metal ions (M n+ ) Between the cathode (base metal) and anode (M metal) electrodes of the plating solution, a high-voltage direct current or high-voltage pulse current that can generate a strong or very strong electric field is applied. The metal ions (M n+ ) Under the action of the electric field, it migrates to the cathode at high speed to obtain a very high energy state, obtains electrons at the cathode, and is deposited on the cathode metal surface to form a metal (M) coating.

[0055] Electrode reaction:

[0056] Cathode reaction:

[0057] Anode reaction:

[0058] Combination Figure 1To further illustrate the present invention: a solution 1 in the form of a coating metal element compound is placed in an insulating, heat-resistant container 2, a soluble metal anode or an insoluble anode 3 and a metal workpiece cathode 4 pre-coated with a coating are placed in the solution 1, respectively, a distance of more than 10 mm is maintained between the two anodes 3 and the cathode 4, and the anode 3 and the cathode 4 are respectively connected to the positive and negative electrodes of a high-voltage pulse power supply 5. Under the action of the pulse voltage applied by the high-voltage pulse power supply 5, a strong electric field with pulse characteristics is generated between the anode 3 and the cathode 4, and the metal cations in the solution obtain energy under the action of the strong electric field, are captured by the cathode 4 in a high-energy state and deposited on the surface of the cathode workpiece 4, forming a metal coating with a dense structure and strong bonding performance with the substrate. The present invention is characterized in that a pulse voltage of 100-3000V is applied between the anode 3 and the cathode 4. Under the action of the high potential electric field, the metal cations in the solution can obtain energy of up to 3000eV. Such high-energy ions bombard the metal parts of the cathode 4, which not only improves the bonding performance between the coating and the substrate, but also makes the coating denser, thus overcoming the problems of the current electroplating coating, such as low bonding strength between the coating and the substrate, loose coating, and inability to deposit thick coatings.

[0059] The microstructure of the thick coating deposited on the metal surface obtained in this embodiment is shown in Figure 2 As shown, Figure 2 As shown, the thick coating obtained by the copper deposition process 3 has a dense structure, no tiny pinholes in the coating, no cracks in the coating, and no deformation of the substrate.

[0060] The thick coating obtained by liquid deposition on the metal surface in this example is applied in composite materials.

[0061] The composite material is a steel-copper composite material.

[0062] The composite material of this embodiment is used in high-end equipment, including marine equipment such as ships and warships, wind turbines, and nuclear power plant equipment.

[0063] Example 2

[0064] A method for depositing a thick coating on a metal surface by liquid phase deposition,

[0065] Nickel deposition example:

[0066] There is no need for pre-nickel plating to deposit a nickel layer on the surface of steel metal parts, and a high-quality nickel layer can be directly deposited on the surface of the steel parts.

[0067] Cathode: Steel metal parts;

[0068] Anode: electrolytic nickel plate;

[0069] Plating solution formula: nickel sulfate (NiSO 4 ﹒ 6H 2O): 10~50g / L; Nickel chloride (NiCl 2 ﹒ 6H 2 O): 1~5g / L; sodium dodecyl sulfate: 0.05~0.1g / L; cathode current density D k :0.1~0.6A / dm 2 ; Plating solution temperature: 25~40℃.

[0070] Nickel deposition process 1: temperature controlled at 25°C, cathode area 20dm 2 , the main components of the solution: nickel sulfate (NiSO 4 ﹒ 6H 2 O): 10g / L, nickel chloride (NiCl 2 ﹒ 6H 2 O): 1g / L, power pulse frequency is 100Hz, duty cycle is 25%, current intensity is 2A (Dk=0.1A / dm 2 ), the voltage varied from 620 to 650 V, and the deposition time was 120 minutes. The thickness of the deposited nickel was 105 μm, the deposited layer was dense, and the bonding strength (tensile strength) with the substrate was 100 MPa.

[0071] Nickel deposition process 2: temperature controlled at 40°C, cathode area 20dm 2 , the main components of the solution: nickel sulfate (NiSO 4 ﹒ 6H 2 O): 50g / L, nickel chloride (NiCl 2 ﹒ 6H 2 O): 5g / L, power pulse frequency is 1000Hz, duty cycle is 45%, current intensity is 12A (Dk=0.6A / dm 2 ), the voltage varied from 500 to 650 V, and the deposition time was 160 minutes. The thickness of the deposited nickel was 210 μm, the deposited layer was dense, and the bonding strength (tensile strength) with the substrate was 120 MPa.

[0072] Nickel deposition process 3: temperature controlled at 30°C, cathode area 20dm 2 , the main components of the solution: nickel sulfate (NiSO 4 ﹒ 6H 2 O): 25g / L, nickel chloride (NiCl 2 ﹒ 6H 2 O): 2g / L, power pulse frequency is 2000Hz, duty cycle is 80%, current intensity is 4A (Dk=0.2A / dm 2 ), the voltage varied from 100 to 210 V, and the deposition time was 190 minutes. The thickness of the deposited nickel was 280 μm, the deposited layer was dense, and the bonding strength (tensile strength) with the substrate was 156 MPa.

[0073] The thick coating obtained by liquid phase deposition on the metal surface in this embodiment has a dense structure, no tiny pinholes in the coating, no cracks in the coating, and no deformation of the substrate.

[0074] The thick coating obtained by liquid deposition on the metal surface in this example is applied in composite materials.

[0075] The composite material is a steel-nickel composite material.

[0076] The composite material of this embodiment is used in high-end equipment, including marine equipment such as ships and warships, wind turbines, and nuclear power plant equipment.

[0077] Example 3

[0078] A method for depositing a thick coating on a metal surface by liquid phase deposition,

[0079] Chromium deposition example:

[0080] Output waveform: square wave;

[0081] Cathode: Steel metal parts;

[0082] Anode: powder metallurgy chromium plate;

[0083] Plating solution formula: chromic anhydride (CrO 3 ): 10~60g / L; sulfuric acid (H 2 SO 4 ): 0.3~0.4g / L; cathode current density D k :0.5~0.7A / dm 2 ; Plating solution temperature: 45~55℃.

[0084] Chromium deposition process 1: Temperature controlled at 45°C, cathode area 10dm 2 , the main components of the solution: chromic anhydride (CrO 3 ): 10g / L, sulfuric acid (H 2 SO 4 ): 0.3g / L, power pulse frequency is 200Hz, duty cycle is 35%, current intensity is 5A (D k =0.5A / dm 2 ), the voltage varied from 780 to 790 V, and the deposition time was 90 minutes. The thickness of the deposited nickel was 102 μm, the deposited layer was dense, and the bonding strength (tensile strength) with the substrate was 80 MPa.

[0085] Chromium deposition process 2: Temperature controlled at 55°C, cathode area 10dm 2 , the main components of the solution: chromic anhydride (CrO 3 ): 60g / L, sulfuric acid (H 2 SO 4): 0.4g / L, power pulse frequency is 1800Hz, duty cycle is 60%, current intensity is 7A (D k =0.7A / dm 2 ), the voltage varied from 650 to 660 V, and the deposition time was 115 minutes. The thickness of the deposited chromium was 110 μm, the deposited layer was dense, and the bonding strength (tensile strength) with the substrate was 95 MPa.

[0086] Chromium deposition process 3: Temperature controlled at 50°C, cathode area 10dm 2 , the main components of the solution: chromic anhydride (CrO 3 ): 40g / L, sulfuric acid (H 2 SO 4 ): 0.35g / L, power pulse frequency is 1200Hz, duty cycle is 55%, current intensity is 6A (D k =0.6A / dm 2 ), the voltage varied from 560 to 570 V, and the deposition time was 200 minutes. The thickness of the deposited chromium was 130 μm, the deposited layer was dense, and the bonding strength (tensile strength) with the substrate was 128 MPa.

[0087] The thick coating obtained by liquid phase deposition on the metal surface in this embodiment has a dense structure, no tiny pinholes in the coating, no cracks in the coating, and no deformation of the substrate.

[0088] The thick coating obtained by liquid deposition on the metal surface in this example is applied in composite materials.

[0089] The composite material is a steel-chromium composite material.

[0090] The composite material of this embodiment is used in high-end equipment, including marine equipment such as ships and warships, wind turbines, and nuclear power plant equipment.

[0091] Comparative Example 1

[0092] The difference between the copper deposition process 1 of this comparative example and the embodiment 1 is that the voltage varies from 5 to 50V.

[0093] In Comparative Example 1, due to low voltage, low concentration of electroplating solution and low electroplating temperature, a plating layer cannot be formed on the metal surface.

[0094] Comparative Example 2

[0095] The only difference between the copper deposition process 1 of this comparative example and the embodiment 1 is that the voltage varies from 5 to 50 V and the temperature is controlled at 80° C.

[0096] In Comparative Example 2, due to low voltage and low concentration of electroplating solution, although the electroplating temperature was increased, only a plating layer of about 5 μm could be formed on the metal surface. Moreover, the plating layer was loose and spongy.

[0097] Comparative Example 3

[0098] The difference between the copper deposition process 1 of this comparative example and the copper deposition process 1 of the embodiment 1 is that the voltage varies from 5 to 50 V and the temperature is controlled at 80° C. The main components of the electroplating solution are copper sulfate (CuSO 4 ﹒ 5H 2 O): 100 g / L, sulfuric acid (H 2 SO 4 ): 20g / L, sodium dodecyl sulfate: 5g / L.

[0099] In Comparative Example 3, due to the low voltage, although the electroplating temperature and electroplating solution concentration were increased, only a plating layer of about 8 μm could be formed on the metal surface. Moreover, the plating layer was loose and spongy.

[0100] It should be understood that in order to streamline the present disclosure and aid in understanding one or more of the various inventive aspects, in the above description of exemplary embodiments of the present invention, various features of the present invention are sometimes grouped together into a single embodiment, figure, or description thereof. However, this disclosed method should not be interpreted as reflecting the intention that the claimed invention requires more features than those expressly recited in each claim. Rather, as reflected in the claims, inventive aspects lie in less than all of the features of the previously disclosed embodiments. Therefore, the claims that follow the detailed description are hereby expressly incorporated into the detailed description, with each claim itself serving as a separate embodiment of the present invention.

[0101] Although the present invention has been described according to a limited number of embodiments, it will be apparent to those skilled in the art, with the benefit of the above description, that other embodiments may be envisioned within the scope of the invention thus described. In addition, it should be noted that the language used in this specification is selected primarily for readability and teaching purposes, rather than for explaining or defining the subject matter of the present invention. Therefore, many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the appended claims. The disclosure of the present invention is illustrative, not restrictive, with respect to the scope of the present invention, which is defined by the appended claims.

[0102] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for depositing a thick coating on a metal surface from liquid phase, characterized in that: The following steps are involved: S01, cleaning and drying the base metal; S02, in a low temperature, low concentration of metal ions M n+ A strong electric field generated by 100-3000V high-voltage pulse electricity is applied between the two electrodes of the base metal and the M metal in the plating solution; the distance between the base metal and the M metal is kept greater than 10mm; S03, after the deposition is completed, a thick metal coating with a dense structure and strong bonding with the substrate is obtained.

2. The method for liquid phase deposition of thick coating on metal surface according to claim 1, characterized in that: The low temperature is 24-26℃, 25-40℃ or 45-55℃.

3. The method for liquid phase deposition of thick coating on metal surface according to claim 1, characterized in that: The M metal is a soluble metal anode or an insoluble anode; the base metal is a steel metal part cathode; the anode and the cathode are respectively connected to the positive electrode and the negative electrode of a high-voltage direct current or high-voltage pulse power source.

4. The method for liquid phase deposition of thick coating on metal surface according to claim 1, characterized in that: Metal ion M n+ Including copper ions, nickel ions or chromium ions.

5. The method for liquid phase deposition of thick coating on metal surface according to claim 1, characterized in that: Metal ion M n+ The concentration is not more than 60g / L.

6. The method for liquid phase deposition of thick coating on metal surface according to claim 1, characterized in that: The thickness of the thick coating is greater than 100 μm.

7. The method for liquid phase deposition of thick coating on metal surface according to claim 1, characterized in that: Method for depositing a copper coating, cathode: steel metal part; Anode: pure copper plate; plating solution formula: copper sulfate CuSO4﹒5H2O: 1~5g / L; sulfuric acid H2SO4: 0.2~0.6g / L; sodium dodecyl sulfate: 0.05~0.1g / L; cathode current density D k :0.1~0.4A / dm 2 ; Bath temperature: 24-26°C; Deposition time: 130-300 minutes; The thickness of the deposited copper metal is 116-590 μm, the deposited layer is dense, and the bonding strength with the base metal is greater than 70 MPa; Method for depositing nickel coating, cathode: steel metal part; Anode: electrolytic nickel plate; plating solution formula: nickel sulfate NiSO4﹒6H2O: 10~50g / L; nickel chloride NiCl2﹒6H2O: 1~5g / L; sodium dodecyl sulfate: 0.05~0.1g / L; cathode current density D k :0.1~0.6A / dm 2 , plating solution temperature: 25-40°C; deposition time is 120-190 minutes; the thickness of the deposited metal nickel is 105-280 μm, the deposited layer is dense, and the bonding strength with the base metal is greater than 100 MPa. Method for depositing chromium coating, cathode: steel metal part; Anode: powder metallurgy chromium plate; plating solution formula: chromic anhydride CrO3: 10 ~ 60g / L; sulfuric acid H2SO4: 0.3 ~ 0.4g / L; cathode current density D k :0.5~0.7A / dm 2 ; Plating solution temperature: 45-55°C; deposition time: 90-200 minutes; the thickness of the deposited metal nickel is 102-130 μm, the deposited layer is dense, and the bonding strength with the base metal is greater than 80 MPa.

8. A thick coating on a metal surface obtained by a method for depositing a thick coating on a metal surface by liquid phase deposition according to any one of claims 1 to 7, characterized in that: The bonding strength between the thick coating and the base metal is 70-156 MPa, and the thickness of the coating is 102-590 μm.

9. Use of the thick coating deposited on a metal surface by liquid phase deposition according to claim 8 in a composite material.

10. The use according to claim 9, characterized in that: Composite materials include steel-copper composite materials, steel-nickel composite materials, and steel-chromium composite materials.